On the Hamming Distance of Repeated-Root Cyclic Codes of Length 6ps - Hai Q. Dinh (2020)
© 2013 IEEE. Let p be an odd prime, s , m be positive integers such that pm≡ 2 pmod 3. In this paper, using the relationship about Hamming distances between simple-root cyclic codes and repeated-root cyclic codes, the Hamming distance of all cyclic codes of length 6ps over finite field Fpm is obtained. All maximum distance separable (MDS) cyclic codes of length 6ps are established.